Gait of Individual with Visual Impairment: Literature Review - Alemán-Ramírez, Carolina (2019)
The gait in people with visual impairment (PWVI) has several variations that affect functionality and health, especially because it affects the skeletal muscle system. Purpose: perform a literature review in order to analyze the pattern of the walk, as well as the implications it has on individuals with low vision and blindness. Method: a systematic review was carried out in the following databases: SportDiscus with full text, psycINFO, Psychology and Behavioral Sciences Collection, Rehabilitation & Sports Medicine Source, Google Scholar, Research Gate, PubMed. Results: The way of walking is slower in the PWVI, they are cautious in the march, to protect themselves, although the surrounding is clear. The disadvantage of this variable is that people do not walk according to the optimal level of walking according to their age and height (recommended speed), so there would be no economy of movement, in addition, its functionality is also affected. Conclusions: The investigations showed that the PWVI, had atypical marches where they found in some cases greater ranges of movement in the involved joints, or on the contrary diminished movements, indicating small or forced movements, unnatural and therefore greater stress muscle and bone. It is very important the assessment in real situations on the PWVI, to be able to provide them with tools that can help them in their independent roll and accessibility.